Biodegradable Polylactide Supraparticle Powders with Functional Additives for Biomedical Additive Manufacturing (Adv. Funct. Mater. 39/2022). (26th September 2022) - Canziani, Herbert; Hanschmann, Benedikt; Tischer, Florentin; Sommereyns, Alexander; Distler, Thomas; Schramm, Jonas; Hesse, Nicolas; Schmidt, Jochen; Grünewald, Alina; Detsch, Rainer; Boccaccini, Aldo; Maskos, Michael; et al.
Abstract : Biodegradable Polylactide Supraparticle Powders In article number 2205730, Nicolas Vogel and co‐workers show that composite supraparticles form powders of biodegradable polymers and nanoscale bioactive additives with tailored composition. These powders can be applied in the powder bed fusion process to fabricate functional biomaterials by additive manufacturing, for example in bone replacement applications.